(o-Phenyleno)naphthalene diimides: a pink fluorescent chromophore. Issue 38 (27th April 2017) - Ma, Yingjie; Zhang, Xiaojie; Stappert, Sebastian; Yuan, Zhongyi; Li, Chen; Müllen, Klaus
Abstract : ( o -Phenyleno)naphthalene dianhydride7 was synthesized by a six-step reaction. Imidizations of7 led to various diimides8 . Their optical and electrochemical properties hold promise for organic electronics. Abstract : ( o -Phenyleno)naphthalene dianhydride7 was synthesized by a six-step reaction. Imidizations of7 led to various diimides8 . Their optical and electrochemical properties hold promise for organic electronics.